Molecular Rubies in Photoredox Catalysis - Sittel, Steven; Naumann, Robert; Heinze, Katja (Frontiers in Chemistry, 2022)
The molecular rubies [Cr(ddpd)2]3+ and [Cr(tpe)2]3+ and the tris(bipyridine) chromium(III) complex [Cr(dmcbpy)3]3+ as well as the tris(bipyrazine)ruthenium(II) complex [Ru(bpz)3]2+ were employed in visible light-induced radical cation [4+2] cycloaddition (ddpd = N,N’-dimethyl-N,N’-dipyridin-2-ylpyridine-2,6-diamine, tpe = 1,1,1-tris(pyrid-2-yl)ethane, dmcbpy = 4,4’-dimethoxycarbonyl-2,2’-bipyridine, bpz = 2,2’-bipyrazine). Along with an updated mechanistic proposal for the CrIII driven catalytic cycle based on redox chemistry, Stern-Volmer analyses, UV/Vis/NIR spectroscopic and nanosecond laser flash photolysis studies, we demonstrate that the very weakly absorbing photocatalyst [Cr(tpe)2]3+ outcompetes [Cr(dmcbpy)3]3+ and even [Ru(bpz)3]2+ in particular at low catalyst loadings, which appears contradictory at first sight. The high photostability, the reversible redoxchemistry and the very long excited state lifetime account for the exceptional performance and even reusability of [Cr(tpe)2]3+ in this photoredox catalytic system.